Intergenic Sequence between Arabidopsis Caseinolytic Protease B-Cytoplasmic/Heat Shock Protein100 and Choline Kinase Genes Functions as a Heat-Inducible Bidirectional Promoter . Issue 3 (3rd October 2014) - Mishra, Ratnesh Chandra; Grover, Anil
Abstract : Two Arabidopsis genes with a role in thermotolerance are oriented in a head-to-head manner in the genome and the intergenic region between these genes functions as a heat-inducible bidirectional promoter . Abstract: In Arabidopsis ( Arabidopsis thaliana ), the At1g74310 locus encodes for caseinolytic protease B-cytoplasmic (ClpB-C)/heat shock protein100 protein (AtClpB-C), which is critical for the acquisition of thermotolerance, and At1g74320 encodes for choline kinase (AtCK2) that catalyzes the first reaction in the Kennedy pathway for phosphatidylcholine biosynthesis. Previous work has established that the knockout mutants of these genes display heat-sensitive phenotypes. While analyzing the AtClpB-C promoter and upstream genomic regions in this study, we noted that AtClpB-C and AtCK2 genes are head-to-head oriented on chromosome 1 of the Arabidopsis genome. Expression analysis showed that transcripts of these genes are rapidly induced in response to heat stress treatment. In stably transformed Arabidopsis plants harboring this intergenic sequence between head-to-head oriented green fluorescent protein and β-glucuronidase reporter genes, both transcripts and proteins of the two reporters were up-regulated upon heat stress. Four heat shock elements were noted in the intergenic region by in silico analysis. In the homozygous transfer DNA insertion mutant Salk_014505, 4, 393-bp transfer DNA is inserted at position −517 upstream of ATG of the AtClpB-C gene. As a result, AtCk2 loses proximity to three of the four heat shock elements in the mutant line. Heat-inducible expression of the AtCK2 transcript was completely lost, whereas the expression of AtClpB-C was not affected in the mutant plants. Our results suggest that the 1, 329-bp intergenic fragment functions as a heat-inducible bidirectional promoter and the region governing the heat inducibility is possibly shared between the two genes. We propose a model in which AtClpB-C shares its regulatory region with heat-induced choline kinase, which has a possible role in heat signaling.